Pengaruh Motivasi dan Kedisiplinan Terhadap Kinerja Karyawan Panen PT. Sinar Dinamika Kapuas 1 Kabupaten Melawi - Permasi, Defi; Kurniati, Dewi; Suharyani, Anita (Universitas Galuh, 2025)
This study aims to assess the extent to which motivation and discipline influence the performance of harvest employees at PT. Sinar Dinamika Kapuas 1, located in Melawi Regency. A quantitative approach was employed, with primary data collected through questionnaires distributed to 122 employees of the company. The collected data were analyzed using the Structural Equation Modeling (SEM) method, assisted by SmartPLS version 4.0 software to test the formulated hypotheses. The results indicate that both motivation and discipline have a positive and significant impact on employee performance. These findings are expected to serve as input for the company in enhancing employee motivation and discipline to better achieve organizational goals.